Weed communities on monoculture and intercropping cultivation techniques - Eko Widaryanto (Brawijaya University, 2017)
Monoculture and intercropping systems are techniques of controlling weeds in technical culture (ecology). Change in cropping system from monoculture to intercropping may affect the growth of weed species which cause different interaction between weed and plant competition. This research aimed to determine the composition of the weed community on the cultivation of monoculture and intercropping systems between maize, peanuts and cowpea. Treatment tested were G0= without crops (weedy), G1 = maize with planting distance of 80 x 25 cm, G2= maize with planting distance of 100 x 25 cm, G3 = maize with planting distance of 80 x 25 cm (+3 row of peanut), G4 = maize with planting distance of 100 x 25 cm (+ 4 row of peanut), G5= maize with planting distance of 80 x 25 cm (+3 row of cowpea), G6 = maize with planting distance of 100 x 25 cm (+ 4 row of cowpea), G7 = peanut with planting distance of 25 x 25 cm, and G8 = cowpea with planting distance of 25 x 25 cm. The results showed that based on Sum Dominance Ratio (SDR) analysis, the weeds in this study consisted of 17 species, i.e. 11 species of broadleaf weeds, 3 species of sedges weeds, and 3 species of grasses weeds. The intercropping system of maize with planting distance of 100 x 25 cm (+ 4 rows of cowpea) gave lower weed communities than the other treatments. Coefficient Community (C) that ranged from 4.54 to14.64 showed differences of weeds and weed communities when the coefficient was under 75% or communities weed species had equality species in the community compared. Shannon-Wienner Index (H') showed the diversity of weed communities the H' value ranged between 1.29 and 2.18. Weed control in intercropping system with cowpea reduced weed dry weight. While intercropping systems of G3, G4, G5 and G6 suppressed weed dry weight by 15.38, 27.69, 55.38, and 53.85% compared with G2, respectively.